Analisis Peran Foreign Direct Investment (FDI) Sebagai Pemicu Keberhasilan Komersialisasi Inovasi Teknologi di Negara-Negara Asia - Sarli Rahman; Andi oh (COSTING : Journal of Economic, Business and Accounting, 2019)
Innovation activities are important things that must be done by a country, but unfortunately not all countries can do it, especially in the high-tech industry, because it requires a very large investment. This study aimed to analyze the role of FDI as a trigger for the successful commercialization of high technology innovations in Asian countries. Innovation is something that must be done by a country in order to compete in the international market, but most Asian countries have limitations in terms of capital, technology and skills to do it. One of solution that can be done is to attract as much investment from abroad through foreign direct investment (FDI). Of the 49 countries in Asia according to id.wikipedia.org, 21 countries countries have been selected as research samples. From the result of structual equation modeling (SEM) analysis founds that FDI was not able to trigger and boost innovation activities of countries in Asia, as measured through spending on R&D activities, number of patent applications, and research journals published internationally. The role of FDI in Asian countries is more to assist these countries in producing results from innovation activities. Keywords: R&D Expenditures, Number of Patent Applications, Number of journal publications, FDI, High-tech export High-tech export